From outsourcing maintenance in a salmon farming company to in-house management: A Reliability-Centered Maintenance plan - Amador-Cáceres, Belkys; Sobarzo Ibañez, Gabriel; Asencio Cárcamo, Gonzalo (EASI: Engineering and Applied Sciences in Industry, 2023)
Outsourcing is the strategy of contracting another entity to provide a specific service. In the case of the salmon farming company, all equipment maintenance activities were outsourced until September 2022. These outsourcing relationships led to failure because of the following reasons: lack of knowledge, incorrect actions, high response times, high costs, and deficient start-up equipment. The salmon farming company decided to partner with Universidad Austral de Chile to close the gaps in maintenance management. The university oversaw the company's workforce training and led a research project to develop a Reliability-Centered Maintenance plan. The farming company is now responsible for the maintenance plan and the results are promising, reducing unplanned downtime and boosting efficiency.
Keywords: Outsourcing; Maintenance Plan; Reliability-Centered Maintenance